Exploiting the Achilles' heel of cancer: disrupting glutamine metabolism for effective cancer treatment - Yuxin Fan; Yuxin Fan; Han Xue; Han Xue; Zhimin Li; Zhimin Li; Mingge Huo; Mingge Huo; Hongxia Gao; Xingang Guan (Frontiers Media S.A., 2024)
Cancer cells have adapted to rapid tumor growth and evade immune attack by reprogramming their metabolic pathways. Glutamine is an important nitrogen resource for synthesizing amino acids and nucleotides and an important carbon source in the tricarboxylic acid (TCA) cycle and lipid biosynthesis pathway. In this review, we summarize the significant role of glutamine metabolism in tumor development and highlight the vulnerabilities of targeting glutamine metabolism for effective therapy. In particular, we review the reported drugs targeting glutaminase and glutamine uptake for efficient cancer treatment. Moreover, we discuss the current clinical test about targeting glutamine metabolism and the prospective direction of drug development.